Evaluation of thermal energy dynamics in a compacted high-conductivity phase-change material - Darkwa, Jo; Su, O.; Zhou, T. (American Institute of Aeronautics and Astronautics, 2015)
This study evaluates the concept of developing a nondeform phase-change energy storage material possessing higher thermal conductivity and energy storage density through a pressure compaction process. The theoretical and experimental investigations have shown that the technique is able to reduce porosity and increase conductivity and energy storage density of a composite material. Even though there was some measure of plastoelasticity due to decompression, the average porosity was reduced from 62 to 23.8% at a relatively low compaction pressure of 2.8 MPa without any structural damage to the tested sample. The mean energy storage density increased by 97%, and the effective thermal conductivity also increased by 25 times, despite a 10% reduction in its latent heat capacity. There is, however, the need for further development toward minimizing the effect of decompression and achieving stronger energy storage tablets at a relatively low compaction force.